2018
DOI: 10.1007/s10995-018-2546-6
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Hospital Utilization among Massachusetts Women with Intellectual and Developmental Disabilities: A Retrospective Cohort Study

Abstract: Objectives This study examined the risk of postpartum hospital admissions and emergency department (ED) visits among US women with intellectual and developmental disabilities (IDD). Methods We used the 2002-2012 Pregnancy to Early Life Longitudinal Data System and identified deliveries to women with and without IDD. Women with IDD (n = 1104) or case subjects were identified from the International Classification of Diseases and Related Health Problems 9th Revision (ICD-9 CM) codes. The study primary outcome mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Twenty-three studies, representing 8,514,356 women in 19 distinct cohorts (including 1 US study that examined 4 states separately), 50 met our inclusion criteria and were included in the qualitative synthesis. Three articles from Canada [44][45][46] and 9 from the United States representing 3 different investigations (2 using California administrative data, 49,53 5 using the Pregnancy to Early Life Longitudinal Data System, 47,48,56,58,59 and 2 using the Pregnancy Risk Assessment Monitoring System for Rhode Island 57,61 ) used the same data sources and had fully or partially overlapping samples and study periods. Table 3 describes the studies' characteristics.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-three studies, representing 8,514,356 women in 19 distinct cohorts (including 1 US study that examined 4 states separately), 50 met our inclusion criteria and were included in the qualitative synthesis. Three articles from Canada [44][45][46] and 9 from the United States representing 3 different investigations (2 using California administrative data, 49,53 5 using the Pregnancy to Early Life Longitudinal Data System, 47,48,56,58,59 and 2 using the Pregnancy Risk Assessment Monitoring System for Rhode Island 57,61 ) used the same data sources and had fully or partially overlapping samples and study periods. Table 3 describes the studies' characteristics.…”
Section: Study Selectionmentioning
confidence: 99%
“…Studies examined the impact of maternal disability overall (n ¼ 10) 47e50, 53,54,57,61,64,66 or physical (n ¼ 1), 60 sensory (n ¼ 2), 62,65 or intellectual and developmental disabilities separately (n ¼ 10). [44][45][46]51,52,55,56,58,59,63 Of the studies that examined the impact of maternal disability overall, 4 compared an any-disability group with a nodisability referent group, 50,57,61,66 and 6 also reported findings broken down by disability type. 47e49, 53,54,64 Six studies included women with mental health disorders within their any-disability group.…”
Section: Study Characteristics Supplementalmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent population-based cohort study examining postpartum hospital admission among US women found that women with IDD had markedly elevated rates of hospital admission compared with women without IDD throughout the first year post partum 16. Another population-based study reported an increased risk for emergency department (ED) visits and hospital admission, particularly for visits related to psychiatric concerns, within 1–42 days of delivery among Canadian women with IDD 6.…”
Section: Introductionmentioning
confidence: 99%